math/derivatives
posted by bobbo .
Please compute the derivative for g(x)= sqrt x  3/x squared. I know the derivative for sqrt x = x ^1/2

If you mean y = √x  3/x^2?
then y' = 1/(2√x) + 6/x^3
Respond to this Question
Similar Questions

calc
find the derivative of y = sqrt(9  16x) Use the chain rule. First find the derivative of the sqrt, and multiply that by the derivative of what is contained inside. Cake. Use the chain rule. If we have y(x)=sqrt(916x) then y'=d/dx(sqrt(916x))*d/dx(916x) … 
Math(Roots)
sqrt(24) *I don't really get this stuff.Can somebody please help me? 
Calculus
find derivitive of 1/square root of x 1/square root of x = x^(1/2) The derivative is 1/2 x^(3/2) can you keep going on the problem to not have negative exponents? 
Math Help please!!
Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine … 
calculus
Find the length of the arc formed by y = (1/8)(4x^22ln(x)) from x=4 to x=8. I found the derivative of the function and got y'= x(1/4x) Where I'm lost now is after plugging it into the arc length equation: integral of sqrt(1+(x(1/4x))^2). … 
Calculus
Using the derivative definition of f ‘ (x) = (f (x+h) – f (x)) / (h) find the derivatives of the following… 1. f(x) = (2x1) / (x+2) 2. f(x) = sqrt (3x1) 3. f(x) = 3x^4 my answers were: 1. –x+3 2. (3) / [2(sqrt(3x1))] 3. … 
Calculus
Find the derivative of cos(sqrt(e^(x^3)cos(x)) I got sin(sqrt(e^(x^3)cos(x))*((sqrt(e^(x^3)cos(x)) Do I just leave the e^(x^3)cosx alone since it's "e" or do I still have the find the derivative for it? 
Calculus
derivative of ((Sqrt(x+3y)+sqrt(3xy))=(sqrt(21)+sqrt(90)) at point (6,5)google 
math please help!!
For what values of x is the graph of y = 8e^−x^2 concave down? 
Calculus  Integrating
Question: ∫(x^2)/sqrt(x^2+1) u=x^2+1 , x^2= u1, du=2xdx ∫(u1)/sqrt(u) , expand ∫u/sqrt(u)  1/sqrt(u) Integrate: 2/3(u^(3/2))  2u^(1/2) + c My answer: [ 2/3(x^2+1)^(3/2)  2(x^2+1) + c ] When I took the derivative of this …